Chemical Equilibria in Analytical Chemistry The Theory of Acid-Base, Complex, Precipitation and Redox Equilibria - Scholz, Fritz; Kahlert, Heike (Springer International Publishing : Imprint: Springer, 2019)
This book provides a modern and easy-to-understand introduction to the chemical equilibria in solutions. It focuses on aqueous solutions, but also addresses non-aqueous solutions, covering acid-base, complex, precipitation and redox equilibria. The theory behind these and the resulting knowledge for experimental work build the foundations of analytical chemistry. They are also of essential importance for all solution reactions in environmental chemistry, biochemistry and geochemistry as well as pharmaceutics and medicine. Each chapter and section highlights the main aspects, providing examples in separate boxes. Questions and answers are included to facilitate understanding, while the numerous literature references allow students to easily expand their studies.